2023
DOI: 10.1186/s12887-023-03866-w
|View full text |Cite
|
Sign up to set email alerts
|

The genotypic and phenotypic characteristics contributing to high virulence and antibiotics resistance in Escherichia coli O25-B2-ST131 in comparison to non- O25-B2-ST131

Abstract: Background Escherichia coli serogroup O25b-sequence type 131 (E. coli O25-B2-ST131) is considered as multidrug-resistant and hypervirulent organism. There is lack of data about involvement of this pathogen in the children’s infection. In this study, the prevalence, and clonality, virulence capacity, and antibiotic resistance phenotype and genotype of E. coli O25-B2-ST131 compared with non-O25-B2-ST131 isolates were investigated in children with urinary tract infection in Tehran, Iran. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 61 publications
1
0
0
Order By: Relevance
“…In this study, REP-PCR method demonstrated good discriminatory ability in discriminating E. coli isolates belonging to same STs. Similar findings have been previously reported ( Can et al, 2016 ; Hojabri et al, 2019a ; Lienard et al, 2021 ; Shahbazi et al, 2023 ). Although REP-PCR is simple, rapid and cost-effective method, its reproducibility is low and depends on quality of bacterial DNA and the PCR conditions ( Foxman et al, 2005 ).…”
Section: Discussionsupporting
confidence: 93%
“…In this study, REP-PCR method demonstrated good discriminatory ability in discriminating E. coli isolates belonging to same STs. Similar findings have been previously reported ( Can et al, 2016 ; Hojabri et al, 2019a ; Lienard et al, 2021 ; Shahbazi et al, 2023 ). Although REP-PCR is simple, rapid and cost-effective method, its reproducibility is low and depends on quality of bacterial DNA and the PCR conditions ( Foxman et al, 2005 ).…”
Section: Discussionsupporting
confidence: 93%